Characteristics of Humidity-Temperature Changing in the Below-Grade Concrete Structure by Applying Waterproofing Materials on the Exterior Wall - Sang-Mook Chang; Sang-Keun Oh; Deok-Suk Seo; Sung-Min Choi (Advances in Materials Science and Engineering)
The water leakage in an underground space cannot easily be repaired owing to the characteristics of the underground space, which not only causes continuous inconvenience to the apartment residents but also facilitates condensation. Thus, the effects of different waterproofing methods in underground spaces on changes in temperature and humidity should be quantitatively studied to establish strong measures for the condensation issue. In this study, two types of specimens were produced separately by dividing the waterproofing materials applied to underground structures into exterior and interior waterproofing construction methods; thereafter, changes in the temperature and humidity inside the specimens were observed. The test results of the evaluation regarding condensation in underground structures indicated that when exterior waterproofing materials are applied, thermal insulation maintains a steady interior temperature and keeps the humidity at an appropriate level, thereby preventing the creation of an environment conducive to the occurrence of condensation.